In ovo injection of betaine promotes adrenal steroidogenesis in pre-hatched chicken fetuses - Halima Abobaker; Nagmeldin A. Omer; Yun Hu; Abdulrahman A. Idriss; Ruqian Zhao (Poultry Science, 2022)
ABSTRACT: Corticosterone is critical for the maturation and survival of chicken fetus around hatching. Betaine is used as a feed additive in poultry industry to promote growth and mitigate stress. However, it remains unknown whether betaine could affect adrenal corticosterone synthesis in pre-hatching chicken fetuses. In this study, betaine (2.5 mg/egg) was injected into developing chicken fetuses at d 11 of incubation (E11) and its impact on adrenal steroidogenesis was investigated at day 19 (E19). Plasma corticosterone concentration was significantly (P < 0.05) elevated in betaine-treated fetuses, together with increased adrenal expression of melanocortin 2 receptor and steroidogenic acute regulatory protein. Accordingly, the corticosterone biosynthetic enzymes, such as cytochrome P450 family 11 subfamily A member 1, 3β-hydroxysteroid dehydrogenase and cytochrome P450 family 21 subfamily A member 2, as well as cholesterol biosynthesis or regulation-related genes, such as sterol regulatory element-binding protein 1, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase and low-density lipoprotein receptor, were all significantly (P < 0.05) upregulated in betaine group. Meanwhile, steroidogenic factor-1 and glucocorticoid receptor were significantly (P < 0.05) enhanced, whereas expression of dosage-sensitive sex reversal-adrenal hypoplasia congenita critical region on the X chromosome gene, a nuclear receptor known as a repressor of adrenal steroidogenesis, was significantly (P < 0.05) downregulated. Betaine significantly (P < 0.05) increased adrenal expression of genes involved in one-carbon metabolism and DNA methylation, such as S-adenosyl homocysteine hydrolase, betaine-homocysteine-methyltransferase, methionine adenosyl transferase and DNA methyltransferases, yet the promoter regions of most steroidogenic genes were significantly (P < 0.05) hypomethylated. These results indicate that in ovo injection of betaine promotes adrenal glucocorticoid synthesis in chicken fetuses before hatching, which involves alterations in DNA methylation.